Peningkatan Pengetahuan Dan Keterampilan Konseling Vasektomi Menggunakan Manekin, Video, Leaflet, Dan Poster - Rizalanda, Sofyan; Soebadi, Doddy Moesbadianto; Sustini, Florentina (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2019)
Objective: to identify the effect of the use of family planning counseling media on improving vasectomy knowledges and counseling skills.Methods: This article used quasi-experimental method with a non randomized control group pre test - post test design. The research subjects were 35 male heads of the male family planning group divided into mannequin, video, leaflet, poster, and control group. Results: Average variable of knowledges of the male family planning group leader before debriefing was 43.66 and after it became 66.86 with average knowledges in the control namely 43.43, leaflet 68.71, poster 68.57, video 74.29, and mannequin 78.29 (p = 0.0001) or smaller than 0.05. While the average variable of counseling skills before debriefing was 26.74 and after it became 84.00 with the average of them were control group 27.43, leaflet 65.14, poster 70.85, video 72.57, and mannequin 71.57, (p = 0,0001) or smaller than 0.05. Conclusion: The use of family planning counseling medias increase vasectomy knowledges and counseling skills. For knowledges, mannequin is the best media. While the counseling skills, video is the best one.Keywords: counseling skills, knowledges, media